Profile of Patients with Gaster Perforation at Dr. Moewardi General Hospital Surakarta in The Period of January-December 2018 - Imam Hafidh Zaini; Ida Bagus Budhi (HM Publisher, 2021)
Introduction: A gastric perforation is a form of hollow digestive organ perforation in which the entire thickness of the stomach wall is injured. Perforation of hollow organs can be suspected based upon the clinical picture, and the diagnosis becomes obvious through an image of free air on imaging performed. Methods: Data of patient characteristics were observed retrospectively from medical records of patients diagnosed with gastric perforation between January and December 2018. Results: Between January and December 2018, 45 patients with gastric perforation were identified, with data distributed by gender. There were 36 women (80%) and 9 men (20%) in the group. Based on the age group, 32 patients (71%) were distinguished by the age group over 40 years and 13 patients (29 %) under 40 years of age. When viewed from the location of the gastric perforations, it was found that 4 patients (9%) had a perforation in the antrum, 36 patients (80%) in the Prepylorus, and 5 patients (11.2%) in the major curvature. Data on analgesic use revealed 32 patients (71%) had a history of taking analgesics and 13 patients (29%) without a history of taking analgesics. Conclusion: In 2018, the majority of gastric perforation patients at Dr. Moewardi Hospital were female (80%), with the highest age group being over 40 years (71%) and the most gastric perforations occurring in the pylori (80%). The number of patients with gastric perforation who had previously used herbs and analgesics was higher (70%) than those who had not. Thus, the results of this retrospective study are consistent with previous research findings and can be used to continue research into the relationships (correlations) between the aforementioned variables.